Experiences of Educing Blind and Deaf Children in The Study of Interpretive Phenomenological Analysis - Carolus Borromeus Mulyatno; Sandra Bakhita Parada Costa (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
A blind and deaf child has a natural power to relate to other people even in situations and conditions of physical limitations. In relating and communicating with a blind and deaf child, teachers and caregivers need to recognize the child's modality. This study aimed to explore the experience of accompanying and educating a blind and deaf child. This qualitative research used an Interpretative Phenomenological Analysis (IPA) approach and a case study using the interview method to collect data. The case studied was the experience of a teacher in accompanying and educating a blind and deaf student at the Helen Keller Special School (SLB G/AB) Helen Keller, Wirobrajan, Yogyakarta. Helen Keller's thoughts on relationships with children with special needs became the framework for analyzing research data. The results of the study showed that blind and deaf children related to other people by using the senses of touch, smell, and taste. These three senses were modalities and bridges for teachers to build relationships with blind and deaf children in the process of learning and to live together. Affective and empathic attention and relationships become the basis for assisting and educating blind and deaf children.